2022
DOI: 10.1210/clinem/dgac664
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation in Autoimmune Thyroid Disease

Abstract: Graves’ disease and Hashimoto’s disease form part of the spectrum of autoimmune thyroid disease (AITD), to which genetic and environmental factors are recognised contributors. Epigenetics provides a potential link between environmental influences, gene expression and thyroid autoimmunity. DNA methylation (DNAm) is the best studied epigenetic process, and global hypomethylation of leucocyte DNA is reported in several autoimmune disorders. This review summarises current understanding of DNAm in AITD. Targeted DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 129 publications
0
10
0
Order By: Relevance
“…Results from animal studies also suggested that hypothyroidism during the critical period of brain development causes permanent brain functional impairment, which could manifest as ASD‐related traits (Sadamatsu et al, 2006). Moreover, studies showed that TH can also alter DNA methylation patterns, by influencing gene expression, which could potentially contribute to ASD‐related outcomes (Khan et al, 2014; Lafontaine et al, 2023; Martinez et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Results from animal studies also suggested that hypothyroidism during the critical period of brain development causes permanent brain functional impairment, which could manifest as ASD‐related traits (Sadamatsu et al, 2006). Moreover, studies showed that TH can also alter DNA methylation patterns, by influencing gene expression, which could potentially contribute to ASD‐related outcomes (Khan et al, 2014; Lafontaine et al, 2023; Martinez et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated that fT3, a significant hormone in the thyroid, has effects on regulating DNA methylation [31]. This means DNA methylation may not be the direct cause of HT but it was the consequence of abnormal thyroid hormones [32]. We can guess that this might be how HT is inherited.…”
Section: Hashimoto's Thyroiditismentioning
confidence: 97%
“…DNA methylation plays the most significant role in this process [34]. Skewed X chromosome inactivation, which means the inactivation occurred in a higher proportion of cells (≥ 80%) than normal (50%) is suggested to be associated with the pathogenesis of HT, especially in females [32]. Multiple studies showed that a higher prevalence of skewed X chromosomes was found in the blood of patients with autoimmune thyroid disorder than in healthy individuals [35][36][37].…”
Section: Hashimoto's Thyroiditismentioning
confidence: 99%
“…In addition, for a given genetic risk factor in AITD, epigenetic modifications mediated by DNA methylation[ 51 ], histone modifications[ 52 ], and noncoding RNAs[ 53 ] may be necessary to trigger AITD. However, the promoting mechanism of such epigenetic modifications in AITD have not been fully elucidated, and therefore, more research should be done to further investigate their roles in AITD pathogenesis and to develop better diagnostic, prognostic, and therapeutic tools.…”
Section: The Basic Characteristics Of T1dm and Aitdmentioning
confidence: 99%